Targeting Endothelial Cell-Specific Molecule 1 Protein in Cancer: A Promising Therapeutic Approach - Zhang, He; Shen, Yi-Wen; Zhang, Li-Jun; Chen, Jin-Jiao; Bian, Hui-Ting; Gu, Wen-Jie; Zhang, Hong; Chen, Hong-Zhuan; Zhang, Wei-Dong; Luan, Xin (Frontiers in Oncology, 2021)
Despite the dramatic advances in cancer research in the past few years, effective therapeutic strategies are urgently needed. Endothelial cell-specific molecule 1 (ESM-1), a soluble dermatan sulfate proteoglycan, also known as endocan, serves as a diagnostic and prognostic indicator due to its aberrant expression under pathological conditions, including cancer, sepsis, kidney diseases, and cardiovascular disease. Significantly, ESM-1 can promote cancer progression and metastasis through the regulation of tumor cell proliferation, migration, invasion, and drug resistant. In addition, ESM-1 is involved in the tumor microenvironment, containing inflammation, angiogenesis, and lymph angiogenesis. This article reviews the molecular and biological characteristics of ESM-1 in cancer, the underlying mechanisms, the currently clinical and pre-clinical applications, and potential therapeutic strategies. Herein, we propose that ESM-1 is a new therapeutic target for cancer therapy.